Polyphenols in Barringtonia racemosa and their protection against oxidation of LDL, serum and haemoglobin - Kong, Kin Weng; Mat Junit, Sarni; Ismail, Amin; Aminudin, Norhaniza; Abdul Aziz, Azlina (Elsevier Science Limited, 2014)
The polyphenolic profiles and antioxidant activities of the water extracts of Barringtonia racemosa shoots (leaves and stems) were explored. Two methods, freeze drying and air drying, for preparation of the shoots, were also compared. Freeze drying was better as air drying caused 5–41% reduction of polyphenols. Three phenolic acids and three flavonoids were identified, using UHPLC. The descending order of polyphenols in the leaves and stems was gallic acid > ellagic acid > quercetin > protocatechuic acid > rutin > kaempferol. In vitro antioxidant analyses were performed using biological samples. In the LDL oxidation assay, B. racemosa leaf extract (IC50 = 73.0 μg/ml) was better than stem extract (IC50 = 226 μg/ml) at inhibiting the formation of TBARS and lipid hydroperoxides. Similar trends were observed for serum and haemoglobin oxidation. B. racemosa leaf extract was better than its stem extract in delaying the time required to oxidise haemoglobin to methaemoglobin. The high polyphenolic content of B. racemosa shoots could have contributed towards their antioxidative effects.